The effect of the start and finish in the 50 m and 100 m freestyle performance in elite male swimmers - Marinho, D. A.; Barbosa, T. M.; Neiva, H. P.; Moriyama, S.-I.; Silva, A. J.; Morais, J. E. (International Journal of Performance Analysis in Sport, 2021)
The aim of this study was to: (1) verify differences between swimmers of the same competitive level in variables related to the start and finish (50 m and 100 m freestyle); (2) verify if starting and finish variables are responsible for faster race time, and which starting variables are responsible for the start performance in such events. For the 50 m and 100 m freestyle race at the junior European Championships 2019, 86 and 88 male swimmers were analysed, respectively. A set of starting and finishing variables were used for analysis. Both races (50 m: p < 0.001; 100 m: p < 0.001) presented a significant level effect for the final race time. The same trend was observed for the start and finish performances. For both races, hierarchical linear modelling retained the 15 m mark time and finish speed as predictors. The 50 m start retained the reaction time and underwater speed, and the 100 m start retained the reaction time and the water break distance. This indicates the underwater phase of the start is of substantial importance to improve the 15 m mark time. Coaches and swimmers are advised to enhance the start underwater phase, and finish segments to improve the swimmers` performance.